The Global Gaze of Protection, Care, and Power - Samaddar, Ranabir (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2020)
The Global Compacts on Refugees and Migrants have been widely considered as opportunities for the world to reconsider old approaches to refugee and migrant protection. The New York Declaration is global, not only because it emanates from a global institution, but also because of the following aspects, to be detailed in course of this article: First, a single declaration covering subjects of migration and forced migration is an acknowledgment of the reality that the two have deep relations, and that population flows are increasingly mixed and massive, defying neat categorization. Second, the declaration also highlights the limits and/or unwillingness of states to carry primary responsibility of refugees and migrants, and hence opens up the possibility to include the “whole of society,” which is to say the “whole of globe” covering stakeholders including business and commercial segments. Third, the new approach is global because refugees and migrants are conceptualized as subjects of global development. Fourth, migration and refugee “crises” are considered inevitable, hence the need for durable solutions, such as the need for a globally relevant comprehensive response framework. And finally, the article touches on the changing nature of the rights question under such a technological mode of management. These aspects are not discussed separately in order, but in an interrelated way. The article is a post-colonial critique of an emerging global apparatus of care and power.